OIL PALM DEVELOPMENT ON THE TIDAL SWAMP LAND (CASE STUDY RAWAPITU REVITALIZATION PROGRAM KABUPATEN TULANG BAWANG, LAMPUNG) - Sumaryanto; Heri Santoso; Fandi Hidayat (Jurnal Pertanian Tropik, 2015)
Indonesia has around 20.11 million hectares of tidal swamp land area and about 2.07 million hectare is tidal swamp potential. The results of the inventory report BPTP Lampung in 2012 revealed that the area of swamp land in Lampung Province 108 thousand ha consisting of 56 thousand ha of tidal swamp and 52 thousand ha of lowland swamp.The main issues management of tidal swamp land is the water level always changing and the sulfidic or pyrite layer. Application water system design are good enough to prevent it. The rain distribution on Rawapitu about 39-531 mm during 2013-2014 and there were 2-3 month dry season. The fluctuation of water level on piezometer showed that the areal flooded on December 2013 and April 2014. It has affected the oil palm growth although increasing the number of frond, rachis length, and leaf area indeks.